Agrivoltaics—The Perfect Fit for the Future of Organic Photovoltaics. Issue 1 (17th November 2020) - Meitzner, Rico; Schubert, Ulrich S.; Hoppe, Harald
Abstract: This Essay presents a possible pathway for the advancement of organic photovoltaics toward broader commercial success and enlarged market size. This vision aims at broad scale applications in photovoltaic greenhouses and polytunnels, which harvest those portions of the solar spectrum that are not used or required by plants. Based on the assumptions of the Shockley–Queisser–Limit, respectively detailed balance, and the additional postulation of using no absorption in the visible part of the AM 1.5G solar spectrum a power conversion efficiency of ≈17% is theoretically predicted. The suggestion is supported by the existence of a number of organic compounds, which already exhibit a good spectral compatibility with the typical photosynthetic action spectrum of chloroplasts. It is hoped that more suitable materials development shall be triggered and fertilized as a result of this Essay. Abstract : A promising path is suggested for upscaling of organic photovoltaics (OPV) toward true mass application in the form of semi‐transparent OPV embedded in polytunnels or green‐houses. Here their specific properties, that is, offering narrow band absorption in the infrared wavelength range can be used as game changer.